An enhanced approach to QoS-aware resource provisioning and job scheduling in cloud computing - Khan, Md. Modabbir Rahman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.